AWARENESS ABOUT BALANCED FOOD AMONG UNSKILLED HUMAN RESOURCE - Sohail, Shaukat; Farooq, Nasir; Rashid, Haroon -ur-; Jadoon, Huma (Journal of Ayub Medical College Abbottabad, 2002)
Background: This study was carried out at Peshawar about the food habits of daily wages labourers working in the urban area. Methods: One to one interview was conducted with 50 randomly selected daily wages labourers, using structured questionnaire. At the same time specimen of capillary blood was obtained from their fingers tips for haemoglobin measurement. Results: The study revealed that due to lack of awareness and poor socio economic status the daily wages labourers are more prone to malnutrition and iron deficiency anaemia. Conclusion: There is a need of comprehensive health education and a strategy should be designed to provide a food locally available that could fulfill the requirement that occurs due to the deficiency of animal protein in the food of daily wages labourers.